Low serum 25-hydroxyvitamin D levels and secondary hyperparathyroidism in Fontan patients. (17th August 2015) - Holler, Finn; Hannes, Tobias; Germund, Ingo; Emmel, Mathias; Hoyer-Kuhn, Heike; Khalil, Markus; Sreeram, Narayanswami; Udink ten Cate, Floris E. A.
Abstract: Background: Limited data exist on the vitamin D status in Fontan patients. We determined the prevalence and potential risk factors of vitamin D deficiency in this patient subset. Methods and results: Data were collected from 27 Fontan patients (55.6% male, mean age 8.1±5.3 years). Protein-losing enteropathy was diagnosed in six patients (22.2%). Vitamin D deficiency was defined as a serum 25-hydroxyvitamin D level of <20 ng/ml. The neutrophil-to-lymphocyte ratio, a marker of systemic inflammation, was calculated. Associations between laboratory measurements and patient characteristics were explored. Mean serum 25-hydroxyvitamin D level was 14.1±10.4 ng/ml. Vitamin D deficiency was found in 19/27 patients (70.3%). Only skin type was associated with vitamin D deficiency (p=0.04). Hyperparathyroidism was present in 5/21 (23.8%) patients, and was more prevalent in patients with protein-losing enteropathy (p<0.001). Parathyroid hormone levels correlated with parameters of systemic inflammation (neutrophil-to-lymphocyte ratio: r=0.484, p=0.026; relative lymphocyte count: r=−0.635, p=0.002). Vitamin D supplementation significantly increased serum 25-hydroxyvitamin D levels (p<0.0001), and was accompanied by a reduction in parathyroid hormone concentrations (p=0.032). Conclusions: A high prevalence of vitamin D deficiency was found among Fontan patients, independent of age, time after Fontan procedure, ventricular morphology, and presence of protein-losing enteropathy. A potentially important link between parathyroid hormone levels and systemic inflammation is suggested.